2017
DOI: 10.1016/j.athoracsur.2016.06.085
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Surveillance After Proximal Aortic Operations: Is it Necessary?

Abstract: Background Current guidelines for imaging surveillance after proximal aortic repair are not evidence based. This study sought to characterize the incidence and causes of reintervention after proximal aortic operations to provide data to guide the frequency and duration of postoperative surveillance. Methods Data on all patients undergoing proximal aortic operations (ascending, with or without root, with or without aortic valve replacement, or with or without arch) during a 9-year period (n = 869) at a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…We have shown that over a median follow-up of nearly 6 years the aortic arch dimensions following surgery on the proximal aorta in patients with BAV remained unchanged and that surgery for aortic arch dilatation after replacement of the root and ascending aorta is uncommon. This is consistent with recent findings from Iribarne and colleagues [17] who demonstrated a low reintervention rate in patients undergoing proximal aortic surgery, with a freedom from reintervention of 92.9% at up to 9 years. In particular, of the 308 patients with bicuspid aortopathy, only 3 (0.9%) required reintervention during follow-up, although they have not specified whether this was due to arch dilatation.…”
Section: Commentsupporting
confidence: 93%
“…We have shown that over a median follow-up of nearly 6 years the aortic arch dimensions following surgery on the proximal aorta in patients with BAV remained unchanged and that surgery for aortic arch dilatation after replacement of the root and ascending aorta is uncommon. This is consistent with recent findings from Iribarne and colleagues [17] who demonstrated a low reintervention rate in patients undergoing proximal aortic surgery, with a freedom from reintervention of 92.9% at up to 9 years. In particular, of the 308 patients with bicuspid aortopathy, only 3 (0.9%) required reintervention during follow-up, although they have not specified whether this was due to arch dilatation.…”
Section: Commentsupporting
confidence: 93%
“…At least in this intermediate follow-up, there was no real justification for follow-up of the aortic arch. Similarly, two references from the Duke Aortic program [2] and the Mayo Clinic [3] showed similar results without demonstrating a surveillance benefit in these patients; patients with bicuspid aortic valves in particular were free of distal aortic intervention. However, all three of these studies clearly demonstrate the need for ongoing aortic root and valve imaging over time because reinterventions in the roots are not uncommon.…”
Section: Invited Commentarymentioning
confidence: 78%
“…This could ensure the surgeon inserts the stent into the true lumen by angiography. In addition, the hybrid surgery results in 80–100% of false lumen thrombus formation in proximal descending aorta (stented segment) [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%